"False peak" creation in the Flynn Creek marine target impact crater. (19th May 2022) - Bray, V. J.; Hagerty, J. J.; Collins, G. S.
Abstract: Impacts into marine targets are known to create abnormal crater morphologies. We investigate the formation of the ~4 km diameter Flynn Creek marine target impact crater using the iSALE hydrocode. We compare simulation results to topographic profiles, mineral pressure indicators, and breccia sequencing from drill cores to determine the most likely sea depth at this location at the time of impact (~360 Ma, Tennessee, USA): 700–800 m. Both the peak shock pressure produced by the impact and the mechanism(s) of central peak formation differ with sea depth. The large central mound of Flynn Creek could have been produced in three distinct ways, all requiring the presence of an ocean: (1) a relatively cohesive rim collapse deposit that reached the crater center as part of a ground flow and came to rest on top of the existing crater stratigraphy; (2) chaotic resurge of ejecta with the returning ocean that deposited at the crater center; (3) large uplift facilitated by the removal of overburden pressure from a deep ocean. The first two of these mechanisms create "false peaks" in which high‐shock uplifted material and original crater floor are buried beneath > 200 m of relatively low shock material. Our simulations suggest that drilling of marine impact sites might require deeper than expected drill cores, so that any high‐pressure mineralogical indictors at depth can be accessed.